PENGEMBANGAN MEDIA PEMBELAJARAN E-KOMIK CERITA RAKYAT LAHILOTE BERBASIS BUDAYA LOKAL DI SEKOLAH DASAR - Pobela, Mawarda; Pomalingo, Samsi; Pulukadang, Wiwy Triyanty; Katili, Sukri; Cuga, Candra (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to develop an E-Comic learning media for Lahilote Folklore that meets the criteria for eligibility and effectiveness in supporting Local Content learning, especially in regional folklore material for fourth grade students. The method used is Research and Development (R&D) with a 4D development model, which includes the define, design, develop, and disseminate stages. The feasibility test was carried out through validation by experts. The results of the media validation showed a score of 28, which is included in the